2015
DOI: 10.4317/jced.51868
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical efficacy of methylprednisolone and serratiopeptidase for reduction of postoperative sequelae after lower third molar surgery

Abstract: Background Surgical removal of mandibular third molars results in some degree of post-operative pain, swelling and trismus. These can be controlled by proper administration of local anesthesia, careful bone removal, minimal trauma to adjacent soft tissues and administration of methylprednisolone and serratiopeptidase drugs. The aim of the present study was to compare the efficacy of methylprednisolone and serratiopeptidase in controlling post-operative pain, swelling and trismus after surgical removal of impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…The molecular mechanism of serratiopeptidase enzyme action in knee OA is not well organized completely, but it was proved that it dissolves the dead and damaged tissues without harming living tissues [37]. Previous Indian study proved that serratiopeptidase provides anti-inflammation effect postoperatively [38].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism of serratiopeptidase enzyme action in knee OA is not well organized completely, but it was proved that it dissolves the dead and damaged tissues without harming living tissues [37]. Previous Indian study proved that serratiopeptidase provides anti-inflammation effect postoperatively [38].…”
Section: Discussionmentioning
confidence: 99%
“…It has powerful anti-inflammatory properties. Clinical studies have shown that it is effective in reducing swelling and edema and metabolizing scar tissues in the body [3] , [4] and particularly useful for post-traumatic swelling, fibrocystic breast disease and bronchitis [5] , [6] , [7] , [8] . It can digest dead tissue, blood clots, cysts, and arterial plaques [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of extraction was assessed by the index described by Pederson. 6 PRP was placed randomly on one side of 3rd molar extraction socket in the case site and the contralateral site was used as control. Postoperative evaluation of soft tissue healing, pain, swelling and radiologic bone density was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmabutor Pvt Ltd., Uttarakand and distributed by Win-Medicare, New Delhi, India). 6 This served as a hemostyptic, antiedematous agent and prevented infection at surgical site.…”
Section: Methodsmentioning
confidence: 99%